(untitled) (Indonesian Court and Justice Review, 2024)
The Indonesian Constitutional Court plays a pivotal role in interpreting the boundaries between state authority and the constitutional rights of its citizens. This study investigates how the Court has shaped the balance between individual rights and state power through its rulings, particularly in cases involving freedom of expression, religious rights, and state security. Employing a doctrinal approach combined with case analysis, the research explores the Court’s reasoning in resolving tensions between competing constitutional values. The findings demonstrate that the Court often positions itself as a mediator between constitutional guarantees and the realities of political governance. While some rulings have expanded civil liberties, others reflect a deferential stance toward state power, particularly in contexts involving public order or national unity. This duality raises important questions about the Court’s long-term role in consolidating democratic values and protecting minority rights. The novelty of this study lies in its systematic assessment of the Court’s jurisprudence on rights limitations, offering insights into the evolving nature of constitutional interpretation in Indonesia. As debates on authoritarianism, pluralism, and civil liberties intensify, understanding how courts delineate the limits of state power becomes increasingly crucial.